Generative AI ChatGPT in Islamic Economics Education Critical Literacy and Academic Ethics - Laelaturramadani Laelaturramadani (Journal of Knowledge and Collaboration, 2025)
This study explores the utilization of Generative AI, specifically ChatGPT, in Islamic Economics Education, focusing on its impact on students' critical literacy and academic ethics. Employing a qualitative research design through a literature review, this study systematically analyzes relevant academic sources published in the past five years to investigate how AI tools, such as ChatGPT, are being integrated into the learning process in higher education, particularly in Islamic economics programs. The findings reveal that ChatGPT enhances learning efficiency by providing students with immediate access to complex economic concepts and supporting autonomous learning. However, concerns about academic integrity, including risks of plagiarism and reduced originality, were identified as significant challenges. Additionally, the study highlights the importance of developing students’ critical literacy, as excessive dependence on AI-generated content may diminish their independent analytical capabilities. The research underscores the need for clear institutional guidelines and ethical frameworks to regulate AI usage in academic environments, particularly in fields like Islamic economics, where ethical values such as honesty, trustworthiness, and responsibility in knowledge acquisition are central. Based on these findings, the study recommends further research into the long-term effects of AI on students' intellectual development and the creation of pedagogical strategies that encourage responsible AI use while preserving academic integrity.